(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The Present study is an effort to know the relationship of self-efficacy with the emotional suffering of the individual’s .It can be further used to control the impact of depression and parenting style on the individuals. In this study the researcher examined the level of self-efficacy and its relation with individuals behavior, attitude, health etc.. The researcher examined the self-efficacy and Adolescents behaviour exposed to different parenting style. It is also concluded that self-efficacy effect the individual emotions with respect to age, gender and profession as well. Authoritative parents compared to authoritarian or permissive parents may be protected from a number of problematic behavioural outcomes. Authoritative parenting has been positively linked to psychosocial competence, academic success, and fewer internalizing problems .The findings further revealed that mild, moderate and severe depression are negatively related with self-efficacy of an individual. This study can be further useful to researchers, psychologists, counselors etc.